Modelling of colloidal particle and heavy metal transfer behaviours during seawater intrusion and refreshing processes. Issue 22 (24th September 2017) - Tan, Bo; Liu, Shuguang; Dai, Chaomeng; Zhou, Hui; Hui, Zhenquan; Zhong, Guihui; Zhang, Hong
Abstract: The proper management of coastal aquifers commonly requires an understanding of regional mass flow and complete seawater–freshwater circulation. In this study, time series observations of seawater intrusion and refreshing were conducted using a column experiment based on natural flow conditions in coastal groundwater and a sampled medium from a coastal sandy aquifer without chemical treatment. Ranges of hydrodynamic and hydrochemical variables were tested and analysed. The results showed that the zeta potential of suspended colloids in aqueous solution in an aquifer polluted with 0.5 g/kg of heavy metals exhibited an isoelectric point for pH values ranging from 5.70 to 6.07 when freshwater or seawater completely occupied the aquifer pores, which is representative of natural hydrochemical conditions. In this scenario, a high background concentration of heavy metals induced colloidal immobilization. Otherwise, seawater–freshwater circulation enabled colloid mobilization due to ionic strength and pH fluctuations. The migration of multiple heavy metals occurred at a characteristic time of approximately 1 pore volume after each intrusion stage began and when the peak rate of colloid release was reached. At these times, the colloid behaviour determined the quantity and pathway of heavy metal transport. On the basis of the influences of seawater and freshwater interactions, the quantity of mobilized particles generally decreased and was uniformly distributed in each fraction due to particle loss and decreased porous connectivity. We speculate that the decrease in the total surface area of the migratory colloids may cause colloid‐associated heavy metal transport to decrease. The experimental results provide a useful basis for testing coastal groundwater flow and mass transport models because these phenomena require full characterization to precisely evaluate the associated fluxes from the field scale to the microscopic dimension.